Heat capacity measurements on FeAs-based compounds: a thermodynamic probe of electronic and magnetic states - Baker, P; Giblin, S; Pratt, F; Liu, R; Wu, G; Chen, X; Pitcher, M; Parker, D; Clarke, S; Blundell, S (Institute of Physics, 2009)
We report heat capacity measurements of the pnictide materials SmFeAsO1−xFx , NdFeAsO, LaFeAsO1−xFx and LiFeAs. For SmFeAsO1−xFx ,with x close to 0.1, we use 3He measurements to demonstrate a transfer of entropy from the peak at TN to a previously unidentified ~ 2K feature, which grows with increasing doping. Our results on the Sm samples are compared with a similarly doped La sample to elucidate the crystal field levels of the Sm3+ ion at 0, 20 and 45 meV, which lead to a Schottky-like anomaly, and also show that there is a significant increase in the Sommerfeld coefficient γ when La is replaced by Sm or Nd. The lattice contribution to the heat capacity of the superconducting oxypnictides is found to vary negligibly with chemical substitution. We also present a heat capacity measurement of LiFeAs showing the feature at Tc, which is significantly rounded and much smaller than the BCS value.